Learning media calculating perimeter of plane figures in edugame for elementary school - Dwi Nugraheny; Riski Mulia Prakasa; Novera Marsda Riny (Institut Teknologi Dirgantara Adisutjipto, 2021)
In computer-based learning process, there are communication process that goes between user; students and the sistem. Calculating perimeter of plane figures in edugame is a learning media that can help students to study and play just in the same time. This edugame is intended to help students understanding and calculating the perimeter of various plane figures way easier with the visualization. Source of the data is from primary and secondary datas of 7th Tematic Elementary School book and several journals about the theory of calculating plane figures. The application’s trial is using questionnaire with correspondents of 17 expert users that are elementary school teachers, with the average result 2.8, which is the interval score criteria as ”good”. Meanwhile, the second trial using youtube as a platform has 64 viewers and 16 comments. The average comments by users are ”This application is very useful”.